INNOVATION OF THE INTEGRATED AND INTEGRATED INFORMATION SERVICE GATE (GAYATRI) AT DEPARTMENT OF HEALTH POPULATION CONTROL AND FAMILY PLANNING IN MOJOKERTO CITY - Arya Pranata Wijaya; Trenda Aktiva Oktariyanda (Publika, 2022)
The Mojokerto City Health Population Control and Family Planning Department in 2019 created an innovative Integrated and Integrated Information Service Gate (Gayatri). Prior to Gayatri, health data reporting used excel reports and each field collected its own data, thus causing data discrepancies. Since the creation of Gayatri, health data has become centralized, collective and real time. Gayatri also presents a feature to make it easier for the people of Mojokerto City to get health services online. The study aims to explain Gayatri's innovation with a research focus using the theory of measuring e-government quality based on the user perspective according to Kozak which consists of six indicators namely ease of use, information content and display, reliability, community support, trust/security, and support in filling out forms. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and documentation. The results show that on the ease of use indicator, Gayatri has a simple and easy to use navigation. On the indicators of content and information display, Gayatri has a simple display and consists of features for the community and features for the Mojokerto City government. In terms of reliability, Gayatri can be accessed via a computer or smartphone, and is available in the form of an application that can be downloaded from the play store. On the indicator of community support, Gayatri provides a whatsapp-based online chat feature. On the indicators of trust/security, Gayatri uses an SSL system and a firewall, and applies encryption to incoming data, to access the database only using a local IP. On the indicators of support in filling out forms, Gayatri supports filling out forms in the online puskesmas registration feature and the community data collection feature. It is hoped that the socialization of Gayatri will be further improved and a blend of usage features will be added to make it easier for people to use it.